Capacitación y su incidencia en el desempeño laboral del personal de la Ferretería ‘‘Bonilla’’ en el cantón La Maná, 2022. - Abreo León, Jusneydi Fernanda (2022)
The purpose of the research project that was carried out in the "Bonilla" hardware store in La Maná canton was to get a descriptive study between the training and work performance of the organization's staff. The methodological direction of the research was quantitative, the application of the analytical and deductive methods were also mandatory and necessary. For the development, data collection, and statistical information, it was necessary to apply surveys to 34 workers, so reaching results on the relevant aspects due to the lack of training which leads to negative effects such as difficulties in employees with low skills and knowledge in their work performance thus affecting the productivity of the company. In the same way, the owner of the company was surveyed who provided the necessary information in order to identify the existing correlations between the study variables, training, and work performance. The obtained results determine that 79.4% of the workers indicate that training is rarely carried out to enhance their skills and performance. In relation to the necessary resources to facilitate a good labor education in the company, the owner states that the company does not have specific tools and methodologies to improve the performance of the staff, however the owner considers that efficient performance will always be essential for the execution of suitable work activities. According to the skills after training, 88.2% consider that training is always efficient, 82.4% affirm that the employees always have an excellent performance after training, and 100% state that constant training will always give employees higher performance in their jobs.